Deterioro Cognitivo tras Administracion de Dosis Subumbrales de Pilocarpina (2016)
INTRODUCTION: The present study sought to determine if there is deterioration cognitive function in Wistar rats to which a single subthreshold dose of pilocarpine and that were evaluated using an object recognition test. MATERIAL AND METHODS: Wistar rats (255±34 g) obtained from the National Institute of Health and kept in the stable in pairs at a constant temperature (24º±1) with water and food ad libitum, they were divided into two experimental groups; Group A (control) to which a single dose of physiological solution was injected (0.9% in 0.5 ml, i.p) and Group B (experimental) to which a single subthreshold dose of pilocarpine (200 mg/kg in 0.5 ml, i.p) long-term memory was evaluated by test object recognition.